SIMILARITIES AND DIFFERENCES BETWEEN "BEOWULF" AND "RAVSHAN" EPICS IN TERMS OF CHARACTER AND THEME. - Fayzullayeva Xushnura; Qosimova Feruza (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Narratives involving heroic figures, legendary creatures, and epic conflicts have enthralled listeners throughout history and space, contributing to the cultural fabric of various communities. The epics of Beowulf and Ravshan are two examples of timeless stories that have endured across centuries and continents, demonstrating the powerful influence of storytelling and the incarnation of heroic ideals in various cultural contexts.